Interpreting the Elements of Halal Tayyiban into Regional Development: The Case of the Siak Regency - Loekman, Agus Suyitno; Perdana, Firdaus Fanny Putera (International Journal of Business Studies, 2024)
This paper examines the integration of Halalan Tayyiban principles within the sustainable development policies of Siak Regency, Indonesia. The regency was recognized as a "Green Regency" in 2016 for its environmental initiatives. It explores the alignment of these Islamic ethical teachings with Siak's jurisdictional approach to achieving socio-economic and environmental sustainability. The methodology involves a comprehensive literature review and thematic analysis of secondary data. The discussion highlights the potential of incorporating Halalan Tayyiban to strengthen environmental sustainability, promote social equity, and enhance economic development. The discussion also acknowledges the challenges such as regulatory complexity and cultural sensitivities. Recommendations include streamlining regulatory processes, fostering interfaith dialogue, leveraging market differentiation, and investing in community education. Future research directions are proposed to quantify the impact of Halalan Tayyiban principles on sustainability outcomes and explore the scalability of Siak's model. The study contributes to the topic of enhancement regarding sustainable development within Islamic ethics and offers insights for regions seeking to integrate traditional wisdom with modern governance.